Spectral Efficiency Evaluation for Channel Estimation Techniques in Massive MIMO Time Division Duplexing (TDD) System - Vuong, Hoang Nam; Nguyen, Van Son (Old Journal, 2019)
Today, a revolution in cellular network has been set in motion toward 5G. One of the key techniques for 5G is massive multiple-input multiple-output (m-MIMO) technology to achieve multiple orders of spectral and energy efficiency gains over current LTE networks. M-MIMO is a system where a base station (BS) with a large number of antennas simultaneously serves many user terminals, each having a single antenna, in the same time-frequency resource. Channel estimation is crucial for M-MIMO systems to provide significant improvement in spectral and energy efficiency. In uplink training the user sends orthogonal pilot signals that are known to the BS then the BS estimates the channel. In this paper, we study several channel estimation techniques in multi-cell massive MIMO time division duplex (TDD) systems. Simulations were performed for several channel estimation techniques in order to identify the best spectral efficiency.